Play, Playfulness, Creativity and Innovation / [electronic resource] - Bateson, Patrick; Martin, Paul (Cambridge : Cambridge University Press, 2013)
What role does playful behaviour and playful thought take in animal and human development? How does play relate to creativity and, in turn, to innovation? Unravelling the different meanings of 'play', this book focuses on non-aggressive playful play. The authors emphasise its significance for development and evolution, before examining the importance of playfulness in creativity. This discussion sheds new light on the links between creativity and innovation, distinguishing between the generation of novel behaviour and ideas on the one hand, and the implementation of these novelties on the other. The authors then turn to the role of play in the development of the child and to parallels between play, humour and dreaming, along with the altered states of consciousness generated by some psychoactive drugs. A final chapter looks forward to future research and to what remains to be discovered in this fascinating and important field.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Creative ability; Creative thinking